WAYS TO IMPROVE THEORETICAL AND PRACTICAL FEATURES OF MONETARY POLICY (Academicia Globe: Inderscience Research, 2021)
This article analyzes the theoretical and practical aspects of monetary policy in various countries around the world and identifies their specific features.